A linear charge pump with novel adaptive charge compensation structure for transient-response improvement in CMOS image sensors. (April 2022) - Gao, Jing; Li, Rui; Nie, Kaiming; Xu, Jiangtao
Abstract: In this paper, a fully integrated, linear-regulated charge pump system is proposed, which improves transient-response for CMOS image sensors. An adaptive charge compensation structure is designed to accelerate the recovery of the output when an undershoot occurs. The proposed charge pump system is designed with 0.11 μm CMOS process, and its area is 0.078 mm 2 . In the post-layout simulation, the worst steady-stable ripple is 0.72 mVPP and the recovery time (99.9%) of the output is 93.012 ns when the undershoot is 111.47 mV. Compared with the traditional structure, the recovery time of the proposed structure is reduced by 57%. The total power consumption of the proposed charge pump is 1.563 mW, and the adaptive charge compensation structure only consumes 69.745 μW. Highlights: A linear-regulated charge pump system for image sensor is proposed. The charge pump system has good transient performance and low output ripple. An energy loss model of switch capacitor charge pump is established. The adaptive charge compensator improves the transient performance of system.